The Design of Economic Incentives for More cost-Effective European Agri-Environmental Measures - Vergamini, Daniele <1983> (Alma Mater Studiorum - Università di Bologna, 2016)
We compare the cost-effectiveness of two simulated auction models (AM1, AM2) with that of classical payment mechanisms as a marginal flat rate payment (MFR) and average flat rate payment (FR). The models follows the one-shot budget constrained auction model first introduced by Latacz-Lohmann and Van Der Hamsvoort (1997), and subsequently by Viaggi et al. (2008) and Glebe (2008). The first model (AM1) deals with one-dimensional bids and it allows farmers to make an offer about a per hectare agri-environmental payment that they would like to receive in order to implement a generic agri-environmental measure on their agricultural land. In the second auction model (AM2) we further extend the analysis, allowing farmers to offer a combination of payment and a measure of their uptake in the agri-environmental program (i.e. a share of their land to commit under the program). Once simulated for AM1 and AM2 the optimal bidding behavior of a population of farmer taken from FADN data of E-R 2010 and 2011, assuming a fixed budget level and the sole objective for the public regulator to maximizes farmers participation to the AEM, we analyzed the total payment, the total cost and the total contracted area comparing the result with MFR and FR payment. The results confirm that the auction has the potential to reduce farmers’ information rent when compared with uniform policy instruments. Though the scale of saving depends crucially on auction design hypotheses and farmers' expectation about the maximum acceptable bid cap. The simulation while reflects a number of plausible assumptions, also remains rather simplified and could be improved in further research. However, it can contribute to feed the debate at EU policy level about the role in considering auction design and bidding behaviour so as to limiting the inefficiency related to the actual agri-environmental payments.